Dynamic Behaviors of Contact Lines on Micropillared Hydrophobic Surfaces - Chen-chuan Tan; Zhi-hai Jia; Hui-nan Yang; Tai-min Cai (Advances in Materials Science and Engineering)
The dynamic characteristics of contact lines on inclined micropillared surfaces were investigated in this paper. It was observed that the contact lines varied gradually to a ladder shape with the droplet sliding on micropillared surfaces under Wenzel state. The dynamic deformation of contact lines would be more obvious under Wenzel state and Cassie impregnating state; however it is negligible when the droplet is in one-dimensional scenario. Droplet layers formed during droplet sliding were left behind and evaporated quickly and disappeared. Based on these characteristics, the comparison of experimental data with theoretical models was discussed. It was found that energy barrier played an important role in analyzing wetting characteristics. Because of ignoring the role of energy barrier, the model of sliding angle cannot predict the sliding angle on micropillared surfaces very well, especially when the area fraction is small. This work is helpful to propose a more accuracy sliding angle model.